2019
DOI: 10.7717/peerj.6324
|View full text |Cite
|
Sign up to set email alerts
|

Recent updates on metabolite composition and medicinal benefits of mangosteen plant

Abstract: Background Mangosteen (Garcinia mangostana L.) fruit has a unique sweet-sour taste and rich in beneficial compounds such as xanthones. Mangosteen has been originally used in various folk medicines to treat diarrhea, wound, and fever. More recently, it has been used as a major component in health supplement products for weight loss and promoting general health. This is perhaps due to its known medicinal benefits including as anti-oxidant and anti-inflammation. Interestingly, the publications related to mangoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 100 publications
1
48
0
Order By: Relevance
“…Local people used various parts of Garcinia mangostana Linn. for treatment of diarrhea, wound infection, and fevers (14). Extensive pharmacological activities of mangosteen and its active compounds have been identified in many studies previously.…”
Section: Mangosteenmentioning
confidence: 99%
See 1 more Smart Citation
“…Local people used various parts of Garcinia mangostana Linn. for treatment of diarrhea, wound infection, and fevers (14). Extensive pharmacological activities of mangosteen and its active compounds have been identified in many studies previously.…”
Section: Mangosteenmentioning
confidence: 99%
“…Extensive pharmacological activities of mangosteen and its active compounds have been identified in many studies previously. The effects include anticancer, antibacterial, and antimalarial, as well as for the treatment of Alzheimer's disease (14,15).…”
Section: Mangosteenmentioning
confidence: 99%
“…It is commonly sold in supermarkets and local markets of Southeast Asia (Franco et al 2020). Several food uses were reported by Aizat et al (2019b) such as food products (dried aril, fruit jam, peel drink, yogurt, ice cream, chocolate, and lozenges), animal feed (dairy steer, lactating cows, broiler chicken), and food shell life (spoilage detection and fruit anti-browning).…”
Section: Local Food Usesmentioning
confidence: 99%
“…G. garcinia is also one of Garcinia species. A comprehensive review from Aizat et al (2019b) showed that G. mangostana offers a multitude of economic benefits ranging from technological and biomedical applications to advanced industrial materials. Products derived from G. mangostana are expected to benefit various biomaterial or biomedical industries and local communities, particularly farmers, traders, and consumers worldwide.…”
Section: Economic Importancementioning
confidence: 99%
“…The pericarp of mangosteen is rich in bioactive agents, such as xanthones, flavonoids, procyanidin, and benzophenones, which are said to contribute to its anti-inflammatory, antibacterial, and anticancer effects (Aizat et al, 2018). The percentage of xanthones is high in the pericarp rather than the pulp of the fruit (Sukatta et al, 2013).…”
Section: Introductionmentioning
confidence: 99%